Violence in Southern Sport and Culture : Sacred Battles on the Gridiron - Bain-Selbo, Eric (Springer International Publishing : Imprint: Springer, 2017)
This book discusses violence and its connection with religion, sport and popular culture. It highlights the religious dimensions of violence and the role of violence in the religion and culture of the American South. Extending into popular culture, it then makes the case that sport-particularly American football-is a cultural phenomenon in the South with close ties with religion and violence, and that American football has come to play a central role in the civil religion of the South, fueled in part by its violent nature. The book concludes by drawing important lessons from this case study-lessons that help us to see both religion and sport in a new light. .
Keywords: Social sciences.; Religion and sociology.; Secularism.; elektronické knihy; electronic books